Challenges in the treatment of adnexal mass in pregnancy: A case report - Laurindo Albues Santos, Ygor; Cassia da Cunha Pedroso, Rafaela; Ferreira do Espírito Santo, Gilmar; Lustosa Rei, Patrícia; Pereira Borges, Ulysses; Burachi, Phablo; Machado Scaloppe, Tane; Henrique Bertoleti Ribeiro, Pedro; Baldi, Djulian; Guedes Fernandez, Beatriz (Seven Editora, 2023)
The term "uterine annex" refers to structures anatomically close to the uterus, including fallopian tubes, ovaries, adjacent vessels, ligaments and connective tissues(3) . Therefore, when there is the appearance of an adnexal mass, it is certainly related to tumor originating from the uterine appendages. That said, it is worth remembering that during pregnancy, these tumors are uncommon, with a variation in incidence of only 1 to 10% of the pregnant population(2) and most of these adnexal masses are functional ovarian cysts that usually disappear during pregnancy, being preserved in only 0.7% to 1.7% of cases. (13) Sob esse prisma, o presente trabalho possui o objetivo de relatar um caso raro de gestante com massa anexial, sendo em ovário direito que evoluiu a um quadro atípico de torção e depois revisar informações acerca do tema, focando no desafio do tratamento cirúrgico. DOI: https://doi.org/10.56238/colleinternhealthscienv1-027